PEMBENTUKAN KARAKTER MAHASISWA ANTI KORUPSI SEBAGAI PENYEMAI HARAPAN BARU - Zilla Aprilia Suherman; Edy Soesanto (Adisam Publisher, 2023)
Character is one of the important things that humans have, character is also included in education, namely character education. Character education is important because it determines each individual's moral values, personality, which has an influence on society and the nation. Character education for students is a challenge for most students. Because students play an important and crucial role in sowing the nation's hopes. This research discusses the formation of student character, especially focusing on the role of students as seeders of the nation's hope. This research uses a literature review method, and this type of research is qualitative. The results of this research show that character education plays an important role in forming the character of anti-corruption students, participants were able to explain the meaning of corruption. Corruption must be prevented and eradicated so that it does not affect the value order of the Indonesian nation which refers to state ideology (Eliezar, 2016). Apart from that, participants were able to identify acts of corruption based on experiences in society and organizations. A number of acts of corruption obtained from participants include time corruption, gratuities, increasing purchase prices, bribes, tribute, commissions, etc., and anti-corruption education does not prevent but rather instills several values in students, namely responsibility, discipline, honesty, independence. , courage to use the SCL (Student Centered Learning) method.